On certain univalent class associated with first order differential subordinations - Ibrahim, Rabha (Tamkang Journal of Mathematics, 2011)
In this paper we consider certain differential inequalities and first order differential subordination.We obtain some sufficient conditions for univalense which generalize and refine some previous result.